Penerapan UCD (User Centered Design) Pada Perancangan Sistem Informasi Manajemen Aset TI Berbasis Web di Bid TIK Kepolisian Daerah Kepulauan Riau - Supardianto Supardianto; Arief Binsar Tampubolon (Politeknik Negeri Batam, 2020)
The process of administration and management of assets in the Information Technology and Communication Division is currently using the Microsoft Excel application. This process makes it difficult to trace and control assets. Asset management is also tricky because many inventories of each item or asset originating from other parties are not installed and damaged. This research aims to design and create a web-based IT asset management information system by implementing UCD (user-centered design). This method focuses on the user as the center of application development, such as specify the context of use, specify User and Organizational Requirements, produce design solutions, and evaluate the design. Based on result Usability Testing with System Usability Scale, the IT Asset Management Information system is in the acceptable range for grade Scale with result C while on adjective ratings with good results of 76. Therefore, the IT Asset Management Information system successfully builds a user-friendly system with a good usability level.